ANALISIS PREFERENSI, POLA KONSUMSI, DAN PERMINTAAN TIWUL OLEH KONSUMEN RUMAH MAKAN DI PROVINSI LAMPUNG - Syafani, Tyas Sekartiara; Lestari, Dyah Aring Hepiana; Sayekti, Wuryaningsih Dwi (Lampung University, 2015)
This researchâs aims are to analyze Â preference, patterns of consumption, and factors affecting of tiwulâs demand by consumers at food stall in Lampung Province. The study was conducted in South Lampung District and West Tulang Bawang District. There were four food stalls located at Dayasakti Village, Pulung Kencana Village, and Sidomulyo Village. Food stall sells tiwul as the main menu. There were 60 respondents in this study that was taken by accidental sampling. Data collection was carried out in February - June 2014. The method of analysis in this study is descriptive quantitative and verification analysis. The results showed that preference of tiwul by consumers at food stall in Lampung Province was at medium category. Attributes of tiwul that Â wanted by consumers at stall food was low price (â¤ Rp5,000), blackish brown color, chewy texture, not strong scent, little taste, and close mileage traveled. Consumption patterns of tiwul was as follows: consumption frequency of once to twice per month, usually consumed pure tiwul by the number of average consumption of 932.52 grams, and the reason for eating tiwul was because of the preference. Factors that significantly affected the demand of tiwul by consumers at food stall in Lampung Province was price of chicken gizzard, price of tempe, and ethnic. The side dish of gizzard chicken was as a complementary good and tempe was as a substitution good. Key words: consumption, demand, preference, tiwul